Determinants of the purchase intention of non-fungible token collectibles - Marius Arved Fortagne; Bettina Lis (Journal of Consumer Behaviour, 2023)
Disrupting the concept of ownership in the digital space, non-fungible tokens (NFTs) have created unprecedented market opportunities and captivated millions of investors. Characterized by artificial scarcity and ensured authenticity, the technical implementation establishes novel parameters for digital ownership and collecting, underscoring a research gap where the determinants of consumer behavior are yet to be studied. This paper presents a research model based on the Stimulus-Organism-Response (SOR) model to investigate consumers' purchase intention of NFT-based collectibles (NFTC) for the first time. To develop our model, we identified distinctive NFTC features (functionality, scarcity, aesthetics, and price value) and blockchain characteristics (security and privacy) affecting the utilitarian and hedonic attitude towards NFTC and finally shape NFTC purchase intention. For empirical validation, we conducted an online survey among an NFT-interested target group (N0.167em=0.167em356) and analyzed the results by structural equation modeling with SPSS Amos. Findings indicate that the utilitarian attitude toward NFTC is affected by perceived functionality and price value from the product side, and perceived blockchain security and privacy from the technology side. The hedonistic attitude toward NFTC is shaped by perceived functionality, scarcity, and aesthetics. Both attitudes, utilitarian and hedonistic, demonstrate a significant impact on purchase intention. A subsequent mediation analysis confirms that NFTC and blockchain characteristics have an indirect effect on purchase intention. In the under-investigated interface of blockchain technology, digital ownership, and consumer behavior, this work enriches the digital ownership discourse by demonstrating how NFTC create consumer value through product and technology features.
Keywords: 320